Engineering Cardiovascular Tissue Chips for Disease Modeling and Drug Screening Applications - Chan, Alex H. P.; Huang, Ngan F. (Frontiers in Bioengineering and Biotechnology, 2021)
In recent years, the cost of drug discovery and development have been progressively increasing, but the number of drugs approved for treatment of cardiovascular diseases has been limited. Current in vitro models for drug development do not sufficiently ensure safety and efficacy, owing to their lack of physiological relevance. On the other hand, preclinical animal models are extremely costly and present problems of inaccuracy due to species differences. To address these limitations, tissue chips offer the opportunity to emulate physiological and pathological tissue processes in a biomimetic in vitro platform. Tissue chips enable in vitro modeling of cardiovascular diseases to give mechanistic insights, and they can also be a powerful approach for drug screening applications. Here, we review recent advances in cardiovascular disease modeling using tissue chips and their applications in drug screening.